2016
DOI: 10.1213/ane.0000000000001441
|View full text |Cite
|
Sign up to set email alerts
|

Interfascial Spread of Injectate After Adductor Canal Injection in Fresh Human Cadavers

Abstract: The adductor canal block has become a common analgesic technique in patients undergoing knee arthroplasty. Dispersion of local anesthetic outside the adductor canal through interfascial layers and blockade of smaller nerves that confer innervation to the knee could contribute to the analgesic efficacy of the adductor canal block. We studied the diffusion of local anesthetic mixed with dye after injection into the adductor canal in fresh human cadavers. In all 8 legs, injectate was found in the popliteal fossa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 8 publications
2
30
0
1
Order By: Relevance
“…Injection of 10 mL of dye into the AC did spread consistently via the adductor hiatus into the popliteal fossa and always stained the popliteal vessels. Furthermore, the sciatic nerve was stained in only 1 of 10 cases probably because of injection of a lower volume (10 mL) compared with Goffin et al 18 It can be speculated that an injection of a larger volume would increase the risk of anesthesia of the sciatic nerve with an associated increased risk of fall and reduction of the ability to ambulate. 16 Furthermore, the analgesic effect of a sciatic block after TKA is not even clinically convincing.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Injection of 10 mL of dye into the AC did spread consistently via the adductor hiatus into the popliteal fossa and always stained the popliteal vessels. Furthermore, the sciatic nerve was stained in only 1 of 10 cases probably because of injection of a lower volume (10 mL) compared with Goffin et al 18 It can be speculated that an injection of a larger volume would increase the risk of anesthesia of the sciatic nerve with an associated increased risk of fall and reduction of the ability to ambulate. 16 Furthermore, the analgesic effect of a sciatic block after TKA is not even clinically convincing.…”
Section: Discussionmentioning
confidence: 88%
“…Several studies have reported a spread of injectate to the popliteal fossa after injection into the AC, but none of these studies have assessed whether the injectate reached the popliteal plexus and the genicular branch of the posterior obturator nerve. [15][16][17][18] The latter plays an important clinical role in knee pain after TKA. 3,19,20 The obturator nerve can be anesthetized by an ultrasound-guided subpectineal injection of local anesthetic at the level of the inguinal crease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 While most investigators report a "midthigh" or distal approach to the ACB, 8,9,11,12 the exact location of the block may affect local anesthetic spread to the nerves within and around the adductor canal. [22][23][24] A prior study by Mariano and colleagues 25 comparing proximal and distal ACBs did not show a difference between groups in terms of total opioid consumption; however, it was not powered for this specific outcome. To date, there have been no prospective trials comparing continuous proximal and distal ACBs using opioid consumption as a primary outcome.…”
mentioning
confidence: 95%